Gamification of 2D and 3D Animation Subjects to Improve Learning Outcomes - Hari Sugiharto Setyaedhi (Universitas Pendidikan Ganesha, 2023)
2D and 3D animation is considered by most teachers as a skills-only subject, requiring no theory. It makes students less interested in learning, causing a decrease in learning outcomes. This research aims to develop gamification in 2D and 3D animation subjects to improve student learning outcomes. This research is research into developing the Lee Owens Model to assess the feasibility and effectiveness of gamification. To test feasibility, expert validation was used, while to test effectiveness, the t-test was obtained from the average value of pre-test and post-test trials. This research involved a sample of 60 people. Data collection uses pre-test and post-test, observation, interviews, and questionnaires. The feasibility of developing gamification was declared valid, with the results of material validation being feasible (77%). Second, the results of the validation of learning media are very good (89%). Third, the learning design validation results are very feasible (88%). Fourth, the results of individual trials are feasible (78%), e) the results of small group trials are very feasible (98%), and field trials are very feasible (89%). The t-test results showed a significant (absolute) difference between the mean post-test learning outcomes for the experimental and control classes. It is concluded that gamification has feasibility and effectiveness in improving student learning outcomes.